The view from the ground - Gellhorn, Martha 1908-1998 (Atlantic Monthly Pr., 1988)
Presented for the first time aregs from the tinderboxes across the political horizons of Castro's Cuba, the chambers of the House Committee on Un-American Activities, and a small Mississippi town during the height of the civil rights movement. Atlantic Monthly Press.
Keywords: Geschichte 1900-2000; Civilization, Modern -- 20th century; History, Modern -- 20th century